2012
DOI: 10.1186/1475-2859-11-158
|View full text |Cite
|
Sign up to set email alerts
|

Probing the applicability of autotransporter based surface display with the EstA autotransporter of Pseudomonas stutzeri A15

Abstract: BackgroundAutotransporters represent a widespread family of secreted proteins in Gram-negative bacteria. Their seemingly easy secretion mechanism and modular structure make them interesting candidates for cell surface display of heterologous proteins. The most widely applied host organism for this purpose is Escherichia coli. Pseudomonas stutzeri A15 is an interesting candidate host for environmentally relevant biotechnological applications. With the recently characterized P. stutzeri A15 EstA autotransporter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…The observed fitness cost for cells induced for NB-C-IgAP production, however, indicates that the explanation is meagre protein display, and points to LppOmpA as a more robust anchor in our system. While autotransporters have been reported as successful display anchors in many cases, our results are consistent with several studies where negative effects of autotransporter anchors were observed, with regards to cell viability [ 40 ], membrane integrity [ 41 ] and ultimately on surface display efficacy [ 8 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The observed fitness cost for cells induced for NB-C-IgAP production, however, indicates that the explanation is meagre protein display, and points to LppOmpA as a more robust anchor in our system. While autotransporters have been reported as successful display anchors in many cases, our results are consistent with several studies where negative effects of autotransporter anchors were observed, with regards to cell viability [ 40 ], membrane integrity [ 41 ] and ultimately on surface display efficacy [ 8 ].…”
Section: Discussionsupporting
confidence: 92%
“…Bacterial surface display of enzymatically active proteins is a promising strategy to engineer whole-cell catalysts, enabling simplification of production procedures as well as downstream processes. Even though many surface display systems have been successfully employed since the first bacterial anchors were developed in the 1980s (reviewed in [ 4 ]), unpredictable, cargo-dependent effects hinder rational design and optimization, as exemplified by Nicolay et al [ 8 ] who reported failure to display a number of passenger domains with a previously characterised autotransporter.…”
Section: Discussionmentioning
confidence: 99%
“…ATs have been widely used as an elegant and efficient tool to display exogenous proteins and showed advantages for biotechnology and industrial (if scale up) applications [ 11 ]. However, not all target proteins can be successfully displayed [ 28 ] and till now there have been no universal rule to predict whether a target protein is suitable for AT-based surface display [ 9 ]. Furthermore, there is still lack of a convenient AT-based system for easier genetic operation and high throughput screening of target proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Because ATs combine a relatively simple secretion mechanism with a flexible transport capacity, they have attracted attention as carriers for transport of heterologous proteins to the extracellular milieu (28,29). For this purpose, heterologous sequences have most often been fused directly to the C-terminal ␤-domain or to the N terminus of the passenger domain (27,30,31). We took a slightly different approach, capitalizing on the crystal structure of the Hbp passenger.…”
mentioning
confidence: 99%